Optic Aphasia: A Process of Interaction Between Vision and Language - Beauvois, M F (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 1982)
A neurological syndrome, called in the literature either optic aphasia or visual anomia, is defined in principle as the inability to name visually presented objects, together with the preservation of both the ability to identify them by sight correctly and to name them when they are presented in another sensory modality. This syndrome was first described by Freund in 1889, but since then its existence has been continually questioned. When it is accepted, the most common interpretation of it is in terms of an anatomical visuo-verbal disconnection. However, the precise level of the psychological process impaired remains unspecified. The purpose of this paper is threefold. First, evidence is reported showing that a verbal impairment specific to visually presented objects can be observed, as well as analogous syndromes (e.g. tactile aphasia). Secondly, a particular kind of visuo-verbal impairment is defined and called optic aphasia, to distinguish it from other possible cases of visuo-verbal impairments. This syndrome is defined by the specification of the level of the particular psychological process supposed to be impaired, i.e. a disturbance between visual semantics and verbal semantics, both of which operate normally. Thirdly, three hypotheses concerning the operation of the semantic system in normal subjects are derived from the evidence coming from this syndrome.